Achieving superior superplasticity from lamellar microstructure of a nugget in a friction-stir-welded Ti–6Al–4V joint. (15th March 2015) - Wu, L.H.; Xiao, B.L.; Ni, D.R.; Ma, Z.Y.; Li, X.H.; Fu, M.J.; Zeng, Y.S.
Abstract : A largest elongation of 728% was achieved in a nugget of a friction-stir-welded (FSW) Ti–6Al–4V alloy joint with a fully lamellar microstructure; this is much larger than the maximum elongation ever reported in fusion-welded nuggets (<400%). This superior superplasticity in FSW nugget vs. fusion-welded nugget was mainly attributed to easier globularization of the lamellae with smaller thickness (172 nm) and aspect ratio (8.1) in the FSW nugget during preheating and superplastic deformation.